2007
DOI: 10.1111/j.1349-7006.2007.00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance of DNA methylation patterns in the early phase of hepatocarcinogenesis induced by a choline‐deficient L‐amino acid‐defined diet in rats

Abstract: The authors investigated the DNA methylation patterns of the E-cadherin, Connexin 26 (Cx26), Rassf1a and c-fos genes in the early phase of rat hepatocarcinogenesis induced by a choline-deficient L-amino acid-defined (CDAA) diet. Six-week-old F344 male rats were continuously fed with the CDAA diet, and three animals were then killed at each of 4 and 8 days and 3 weeks. Genomic DNA was extracted from livers for assessment of methylation status in the 5′ ′ ′ ′ upstream regions of E-cadherin, Cx26, Rassf1a and c-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…Cd can also replace zinc in the zinc finger structure via nucleoside excision repair disorder, which has been previously reported (Shimizu et al, 2007). Cd is related to cellular transformation and carcinogenicity (Zhou et al, 2012).…”
Section: Discussionmentioning
confidence: 80%
“…Cd can also replace zinc in the zinc finger structure via nucleoside excision repair disorder, which has been previously reported (Shimizu et al, 2007). Cd is related to cellular transformation and carcinogenicity (Zhou et al, 2012).…”
Section: Discussionmentioning
confidence: 80%
“…In a recent study of the association between maternal glucose concentration and the DNA methylation level in the placenta adiponectin gene, the frequency of adiponectin DNA methylation was correlated with maternal blood glucose levels during pregnancy, insulin resistance, and maternal circulating adiponectin concentrations [14]. Many genes have been found to be highly methylated in the presence of hepatocellular carcinoma [15], but little known about methylation as it relates to NAFLD. Therefore, it is of great value to examine the potential for DNA methylation of adiponectin to slow the progression of NASH.…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation is an epigenetic modification that plays an important role in the control of gene expression in mammalian cells, and aberrant DNA methylation plays an important role in the tumor progression (Calvisi et al, 2007;Choi et al, 2007;Shimizu et al, 2007). Many studies have shown that alterations at the genomic levels and regional changes in the patterns of DNA methylation are commonly observed in the neoplasia at early stages (Baylin et al, 1998;Pogribny and James, 2002).…”
Section: Discussionmentioning
confidence: 99%